In Situ Recyclable Surface-Enhanced Raman Scattering-Based Detection of Multicomponent Pesticide Residues on Fruits and Vegetables by the Flower-like MoS2@Ag Hybrid Substrate - Chen, Ying; Liu, Hongmei; Tian, Yiran; Du, Yuanyuan; Ma, Yi; Zeng, Shuwen; Gu, Chenjie; Jiang, Tao; Zhou, Jun (ACS applied materials & interfaces, 2020)
Pesticides, extensively used in agriculture production, have received enormous attention because of their potential threats to the environment and human health. Hence, in this study, a kind of highly sensitive and stable hybrid surface-enhanced Raman scattering (SERS)-active substrates constructed with flower-like two-dimensional molybdenum sulfide and Ag (MoS2@Ag) has been developed, and then the above substrate was sequentially utilized in the recyclable detection of pesticide residues on several kinds of fruits and vegetables. In the first place, the excellent photocatalytic performance of the MoS2@Ag hybrid substrate was demonstrated, which was attributed to the inhibition of electron–hole combination after the formation of Schottky barrier between the Ag NPs and MoS2 matrix. Thereafter, two calibration curves with ultra-low limits of detection (LOD) as 6.4 × 10–7 and 9.8 × 10–7 mg/mL were established for the standard solutions of thiram (tetramethylthiuram disulfide, TMTD) and methyl parathion (MP), and then the recyclable assay of their single and mixed residues on eggplant, Chinese cabbage, grape, and strawberry was successfully realized. It is interesting to note that the detection recoveries from 95.5 to 63.1% for TMTD and 92.3 to 62.6% for MP are greatly dependent on the size and surface roughness of these foods. In a word, the MoS2@Ag composite matrix shows attractive SERS and photocatalysis performance, and it is expected to have the potential application on food safety monitoring.